The Influence of Fintech E-Wallets and Self-Control on the Consumptive Behavior of Generation Z in Bangkalan: Efforts for Digital Financial Education and Literacy - Rumyati Zeinab; Ruski (Global Action and Education for Society, 2025)
This research is motivated by the increasing use of Fintech E-Wallets among Generation Z university students, which facilitates financial transactions but also has the potential to encourage consumptive behavior, especially when not accompanied by adequate self-control. The purpose of this study is to analyze the influence of Fintech E-Wallet and Self-Control on the consumptive behavior of students in Bangkalan Regency. The method used is a descriptive quantitative approach with survey techniques. Data were collected through questionnaires distributed to 60 students from three universities, selected using purposive sampling. The data were analyzed using multiple linear regression. The results showed that Fintech E-Wallet has a positive and significant influence on consumptive behavior (significance value = 0.001), while Self-Control has a negative and significant influence on consumptive behavior (significance value = 0.003). Simultaneously, both variables significantly affect consumptive behavior (significance value = 0.000). The conclusion of this study is that the ease of digital access through e-wallets can increase the consumptive tendencies of students, but this can be mitigated through strong self-control, indicating the importance of awareness in managing finances wisely.